Laparoscopic Sleeve Gastrectomy or Laparoscopic Gastric Bypass for Patients with Metabolic Syndrome: An MBSAQIP Analysis. Issue 10 (October 2019) - Alizadeh, Reza Fazl; Li, Shiri; Gambhir, Sahil; Hinojosa, Marcelo W.; Smith, Brian R.; Stamos, Michael J.; Nguyen, Ninh T.
In patients undergoing bariatric surgery, the presence of metabolic syndrome (MetS) contributes to perioperative morbidity. We aimed to evaluate the utilization and outcome of severely obese patients with MetS who underwent laparoscopic sleeve gastrectomy (LSG) versus laparoscopic Roux-en-Y gastric bypass (LRYGB). Using the 2015 and 2016 Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program database, data were obtained for patients with MetS undergoing LSG or LRYGB. There were 29, 588 MetS patients (LSG: 58.7% vs LRYGB: 41.3%). There was no significant difference in 30-day mortality (0.1% for LSG vs 0.2% for LRYGB, adjusted odds ratio (AOR) 0.58, confidence interval (CI) 0.32–1.05, P = 0.07) or length of stay between groups (2 ± 2 for LSG vs 2.2 ± 2 days for LRYGB, P = 0.40). Compared with LRYGB, LSG was associated with significantly shorter operative time (78 ± 39 vs 122 ± 54 minutes, P < 0.01), lower overall morbidity (2.3% vs 4.4%, AOR 0.53, CI 0.46–0.60, P < 0.01), lower serious morbidity (1.5% vs 2.3%, AOR 0.64, CI 0.53–0.76, P < 0.01), lower 30-day reoperation (1.2% vs 2.3%, AOR 0.52, CI 0.43–0.63, P < 0.01), and lower 30-day readmission (4.2% vs 6.6%, AOR 0.62, CI 0.55–0.69, P < 0.01). In conclusion, LSG is the predominant operation being performed for severely obese patients with MetS, and its popularity may in part be related to its improved perioperative safety profile.